Basic electricity - Zbar, Paul.; Rockmaker, Gordon; Bates, David; Ferrett, Sharon ([S.l.] : McGraw-Hill Science/Engineering/Math, 1992)
Designed for use in traditional DC/AC courses, this text serves equally well as a stand-alone introductory text and lab manual or as a lab manual for use with any basic theory text. The content of this text/lab manual is prepared with the technical assistance of the Electronic Industries Association, guaranteeing that the material is consistent with the competencies of the electronics manufacturing and service industries.